Application of Deswirl Device in Cyclone Dust Separator - M. Z. Abdullah; Z. Husain; S. M. Fraser (ASEAN Journal on Science and Technology for Development, 2003)
The experimental investigations of the vortex flow inside the vortex finder (outlet duct) of the cyclone dust separator have been carried out.  Preliminary study from the visualization experiment has been performed and discovered vortex instability inside the conventional vortex finder.  In order to minimize the instabilities, the streamlined entry shape was inserted at the vortex finder entrance and the results showed remarkable improvement of the vortex flow instability inside the vortex finder.  The velocity measurements of two main components of velocity were performed using a laser-Doppler anemometry at the cyclone vortex finder outlet.  The experiments were conducted at a constant flow rate of 0.0246m3/s with the vortex finder diameter of 64mm and with several types of entrance configuration in order to improve the cyclone performance and to reduce the losses.  The use of deswirl devices inside the vortex finder significantly reduced pressure drop and energy losses.